Diagnostic accuracy of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in differentiating thyroid tumors: A systematic review and meta-analysis - Bisrat Birke Teketelew; Dereje Mengesha Berta; Elias Chane; Amare Mekuanint; Tekletsadik Tekleslassie Alemayehu; Zewudu Mulatie; Muluken Walle; Abiy Ayele Angelo; Negesse Cherie (PLoS ONE, 2025)
Background Thyroid neoplasms include a range of lesions, most of which are benign, though some may progress to or present as malignant. Diagnostic tools like FNAB, ultrasound, and hormone analysis are commonly used, though they have limitations. Recently, peripheral blood markers have been explored for their potential in differentiating thyroid lesions, despite controversy evidence. This review evaluates the diagnostic utility of NLR and PLR in thyroid lesions. Methods We systematically searched all relevant articles on PubMed, Science Direct, Cochrane Library, and gray literature, including Google Scholar, for studies on the diagnostic utility of platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) in thyroid lesions. Two researchers independently screened articles, and study quality was assessed using the QUADAS 2 tool. A random-effects model calculated pooled sensitivity and specificity, while the area under the HSROC curve summarized diagnostic accuracy. Heterogeneity was evaluated with Higgins’ I² statistic, and publication bias was assessed using the MIDAS command. Subgroup analyses by sample size, gender distribution, cutoff values, and carcinoma types explored sources of heterogeneity. Results A total of 12 studies were included in the final meta-analysis, with 9 focusing on NLR and 6 on PLR. Most of these studies were retrospective in design. The pooled sensitivity and specificity of NLR were 75% (95% CI: 65–82%) and 62% (95% CI: 42–75%), respectively. For PLR, the overall sensitivity and specificity were 70% (95% CI: 61–78%) and 57% (95% CI: 46–66%), respectively. The diagnostic accuracy, based on the area under the HSROC curve (AUC), was 0.75 (95% CI: 0.71–0.79) for NLR and 0.69 (95% CI: 0.65–0.73) for PLR. These results indicate that NLR has better diagnostic accuracy than PLR in distinguishing between benign and malignant thyroid lesions. Conclusion While the NLR demonstrates better diagnostic utility than the PLR in distinguishing between benign and malignant thyroid lesions, its standalone diagnostic accuracy remains moderate. Therefore, we recommend using these markers as complementary tools alongside other standard diagnostic modalities until further studies provide more definitive evidence. Thyroid neoplasm is a type of cancer which arises from the thyroid parenchymal cell and affects the thyroid gland. The disease encompasses a variety of lesion, including benign adenomas to malignant carcinomas [1]. The majority of thyroid glands are noncancerous and are mostly benign. In some contexts, thyroid adenomas may transform into carcinomas as the nonfunctional adenomas possess oncogene mutations [2]. Overall, 5% of thyroid nodules are malignant. Notably, approximately 20% of follicular adenomas have the potential to progress into follicular carcinomas [3]. The common thyroid malignancies include, papillary, follicular, medullary and anaplastic types, which varies based on the aggressiveness of the cancer, which are highly variable clinical features; some may be indolent and slow progressing while others may be highly aggressive tumors with a high mortality rate [4,5]. Globally, thyroid cancer cases are increasing over time. Approximately 18.3 million thyroid cases were reported with a high prevalence rate in China and United States [6]. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was used and performed for this systematic review and meta-analysis. This review was registered on PROSPERO with registration number of CRD42024559798.